A description of the sedimentology and palaeontology of the Late Triassic–Early Jurassic Elliot Formation in Lesotho - Bordy, E. M.; Hancox, P. J.; Rubidge, B. S. (BERNARD PRICE INSTITUTE FOR PALAEONTOLOGICAL RESEARCH, 2004)
Sedimentological studies of the Late Triassic to Early Jurassic Elliot Formation (Karoo Supergroup) in Lesotho have proved to be a fundamental element in our research into the development of the main Karoo Basin of southern Africa. Complementing previous research in SouthAfrica, studies of the architecture of the sedimentary units in the Elliot Formation reveal that there are two contrasting types of sandstone body geometries, each resulting from different fluvial depositional styles. In the lower part of the formation, the sandstones resemble multi-storey channel-fills, interpreted as deposits of perennial, moderately meandering fluvial systems. On the other hand, the upper part of the formation is characterized by mostly tabular, multi-storey sheet sandstones which resulted from ephemeral fluvial processes. Based mainly on changes in the fluvial style and palaeocurrent pattern within the formation, the regional lithostratigraphic subdivision applied to the Elliot Formation in South Africa is applicable in Lesotho as well. This study adds detail and therefore refines the stratigraphic subdivision documented for the South African succession, and as such forms an important framework for palaeontological, palaeoecological and biostratigraphic studies in Lesotho.